The Impact of Macroeconomic Complexity on Environmental Pollution in Indonesia (1989-2024): An Empirical Study Using the Autoregressive Distributed Lag Approach - Deni Wahyudi; Taupiq Chaidir (LP2M IAIN Palopo, 2026)
Environmental pollution caused by increasing carbon dioxide (CO₂) emissions has become an important issue in Indonesia due to rapid economic growth, industrialization, and dependence on fossil fuels. Understanding the relationship between macroeconomic dynamics and environmental degradation is essential to support sustainable development and emission reduction targets. This study aims to analyze the impact of macroeconomic complexity on environmental pollution in Indonesia during 1989-2024 using the Autoregressive Distributed Lag (ARDL) approach. The variables examined include economic growth, interest rates, inflation, foreign direct investment (FDI), energy consumption, and international trade openness on CO₂ emissions. The findings reveal a long-run cointegration relationship among the variables. Economic growth, interest rates, and energy consumption positively and significantly affect CO₂ emissions, indicating that Indonesia remains in the early stage of the Environmental Kuznets Curve (EKC). Meanwhile, international trade openness has a negative and significant effect on emissions through technological efficiency and cleaner production practices. Inflation and FDI show insignificant effects in the long run. These findings highlight the importance of integrating macroeconomic, energy, and environmental policies through renewable energy transition, green investment, and sustainable trade strategies to achieve Indonesia’s emission reduction target by 2030. Keywords: Macroeconomic complexity, Carbon dioxide emissions, ARDL, Sustainability, Renewable energy